1980
DOI: 10.1159/000459235
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Glutaminase Activity during the Growth Cycle of Cultured Human Diploid Fibroblasts

Abstract: The activity of glutaminase per milligram of protein increased threefold after cultured human diploid fibroblasts were subcultured in fresh medium. The maximum activity was reached after 2 days of growth and decreased once the cells reached confluency. The increase of glutaminase activity was independent of the glutamine concentration between 0.2 and 2.0 mmol/1. In contrast, the specific activity of glutamate dehydrogenase was independent both of the glutamine concentration and the growth phase of the cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In stationary-phase cells, however, the activities were clearly decreased by 107% and 367% in both media. Sevdalian et al (1980) found similar results for cultured human diploid fibroblasts. The GLNase activity reached its maximum after 2 days of growth independently of the glutamine concentration (0.2-2.0 mM) and decreased once the cells reached confluency.…”
Section: Glutamine Metabolismsupporting
confidence: 67%
“…In stationary-phase cells, however, the activities were clearly decreased by 107% and 367% in both media. Sevdalian et al (1980) found similar results for cultured human diploid fibroblasts. The GLNase activity reached its maximum after 2 days of growth independently of the glutamine concentration (0.2-2.0 mM) and decreased once the cells reached confluency.…”
Section: Glutamine Metabolismsupporting
confidence: 67%
“…Active glutamine metabolism has been correlated with rapid cellular growth. For example, activity of glutaminase increases 3-fold during log phase growth in human diploid fibroblasts compared to confluent cultures (24). Moreover, glutaminase activity doubles between d 12 and 15 after birth (25).…”
Section: Discussionmentioning
confidence: 99%
“…1, Step1a). The presence and level of simple glutaminase activity, glutamine ~ glutamate + NHt, are strongly correlated with tissues and cells that exhibit high rates of glutamine oxidation (Williams and Manson, 1958;Knox et al, 1967Knox et al, , 1969Linder-Horowitz et al, 1969;Kovacevic, 1974;Pinkus and Windmueller, 1977;Sevdalian et al, 1980;Blitz et al, 1982). Detailed studies on the reaction kinetics and physicochemical properties…”
Section: Glutamine To Glutamate (Fig 1 Step 1)mentioning
confidence: 99%